Estimativa de sedimentos em suspensão utilizando um perfilador acústico de correntes por efeito doppler - OLIVEIRA, Pablo Abreu de (Universidade Federal do Pará, 2019)
In the management of water resources it is of fundamental importance to know the behavior, quality and quantity of sediments transported in river environments. These sedimentometric data are useful in defining various aspects and problem solving of water resources engineering. ADCP (Acoustic Doppler Current Profilers) is a new technology for flow and velocity measurements in rivers through acoustic waves, which may also be covered in sediment concentrations. In this context, the objective of the present work is to verify the applicability of the use of ADCP as an alternative for suspended sediment measurements. For this, the method of Gartner (2002) was used, calibrating its equation with the concentrations obtained by the point sampling method, collected with a bottle of Van Dorn in the Guamá river. The method used to obtain CSS (Suspended Sediment Concentration) with ADCP data resulted in a good estimate of concentrations, supported by the above calibration. There was a good correlation between the sediment concentration measured and the estimated 0.68 for point CSS and 0.81 for the vertical CSS. Through analyzes of the generated data we may affirm that the ADCP may also be used to measure suspended sediments in an indirect way from the return of the acoustic signal.